Ameliorative effects of curcumin against lead induced toxicity in human peripheral blood lymphocytes culture. (2nd January 2018) - Nariya, Ankit; Pathan, Ambar; Shah, Naumita; Chettiar, Shiva; Patel, Alpesh; Dattani, Jignasha; Chandel, Divya; Rao, Mandava; Jhala, Devendrasinh
Abstract: Lead, a heavy metal and multifaceted toxicant, is well studied for its distribution and toxicity in ecosystem, yet there is no consensus on its amelioration by any synthetic or phytochemical compounds. Curcumin, a known antioxidant and dietary element, is a well-known herb, for its therapeutic uses and having a wide spectrum of its beneficial properties against several adverse effects. Hence, the current study was taken into consideration to evaluate the ameliorative effects of curcumin (3.87 μM, i.e. 1.43 μg/ml) against lead acetate (doses: 10 −6 M, i.e. 0.379 μg/ml and 10 −4 M, i.e. 37.9 μg/ml, durations: 24 h and 69 h) induced genotoxicity and oxidative stress in human peripheral blood lymphocyte cultures (PBLC). On one hand, antigenotoxic and antioxidative potentials of curcumin against lead were simultaneously evaluated by the array of genotoxicity and oxidative stress indices. The result postulated that lead acetate showed dose- and duration-dependent increase in both genotoxicity and oxidative stress whereas curcumin, when added along with lead acetate, showed the significant amelioration in all genotoxic and oxidative stress-related indices. The study indicated that, due to alteration in antioxidant defense system, there is an adverse genotoxic effect of lead. On the other hand, curcumin, a potent antidote, can protect chromatin material against lead -mediated genotoxicity by balancing the activity of antioxidant defense system.